2015
DOI: 10.4236/fns.2015.61015
|View full text |Cite
|
Sign up to set email alerts
|

Apple Extracts Present Catabolic and Hipocolesterolemic Effect in Mice

Abstract: Dyslipidemia is highly prevalent in the Chilean population: about 40% have total cholesterol levels over 200 mg/dl and 25% are obese (BMI > 30) which produces an increased risk of cardiovascular disease and deaths. Over consumption of foods rich in lipids and carbohydrates unchains these events, due to the high amount of lipid accumulation in adipocytes. These cells are capable of producing a large number of mediators of inflammation and adipokines which in large quantities can compromise the overall metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This finding is in line with Poblete et al . 's study[ 8 ] who reported a decrease in LDLc and an increase in HDLc after the administration of ethanolic extract of apple peel at a dose of 400 mg/kg BW. Rutin can reduce activities of the acyl-CoA cholesterol transferase enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with Poblete et al . 's study[ 8 ] who reported a decrease in LDLc and an increase in HDLc after the administration of ethanolic extract of apple peel at a dose of 400 mg/kg BW. Rutin can reduce activities of the acyl-CoA cholesterol transferase enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic extract of apple flesh and peels had lowered TC, LDL, and weight of white adipose tissue in hyperlipidemic mice. [ 8 ] Anthocyanins and phenolics content of apple peels may contribute to its antihyperlipidemic activity. [ 9 ] The supplementation of apple peel phenol to hamster for 28 days decreased serum LDLc and HDLc.…”
Section: Introductionmentioning
confidence: 99%